2017
DOI: 10.1261/rna.061044.117
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine is required for the hypoxic stabilization of specific mRNAs

Abstract: Post-transcriptional regulation of mRNA during oxygen deprivation, or hypoxia, can affect the survivability of cells. Hypoxia has been shown to increase stability of a subset of ischemia-related mRNAs, including VEGF. RNA binding proteins and miRNAs have been identified as important for post-transcriptional regulation of individual mRNAs, but corresponding mechanisms that regulate global stability are not well understood. Recently, mRNA modification by N 6 -methyladenosine (m 6 A) has been shown to be involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 83 publications
6
75
0
Order By: Relevance
“…7a and Supplementary File 2 contains an edge list representation of the coexpression network). For example N6-adenosine-methyltransferase non-catalytic subunit (METTL14) is required in hypoxic stabilization of mRNAs [47] This is consistent with the known role of HIF-1α in regulating metabolic switches.…”
Section: Protein Association Network Identify Signaling Components Psupporting
confidence: 79%
“…7a and Supplementary File 2 contains an edge list representation of the coexpression network). For example N6-adenosine-methyltransferase non-catalytic subunit (METTL14) is required in hypoxic stabilization of mRNAs [47] This is consistent with the known role of HIF-1α in regulating metabolic switches.…”
Section: Protein Association Network Identify Signaling Components Psupporting
confidence: 79%
“…Instead, m 6 A seems to be acting by increasing IAV RNA levels by either enhancing viral replication or by enhancing viral RNA stability. Interestingly, while m 6 A has been reported to destabilize RNAs in some settings (Ke et al, 2017; Wang et al, 2014), others have reported that m 6 A can act to stabilize mRNAs (Fry et al, 2017). Of note, we have previously reported that m 6 A residues enhance the expression level of HIV-1 mRNAs as well as indicator plasmid mRNAs bearing m 6 A residues in cis , which may suggest that m 6 A is used by both IAV and HIV-1 to increase the steady state level of viral mRNA expression by a similar, post-transcriptional mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that additional inter-species differences may emerge in processes downstream of transcription. For example, METTL14 deposits the N 6 -methyladenosine RNA modification, which has been implicated in the stabilization of mRNA molecules following hypoxia (Fry et al 2017). Intriguingly, differences in N 6 -methyladenosine levels have been reported between primates ).…”
Section: Inter-species Differences In Response To Oxygen Perturbationmentioning
confidence: 99%